Consumer Adoption of New Products: Independent versus Interdependent Self-Perspectives - Ma, Zhenfeng; Yang, Zhiyong; Mourali, Mehdi (Journal of Marketing, 2014)
In five studies, the authors examine the impact of an independent (vs. interdependent) mindset on consumer adoption of new products. Study 1 demonstrates that consumers in a predominantly independent (vs. interdependent) culture are more willing to adopt really new products, whereas consumers in a predominantly interdependent (vs. independent) culture are more willing to adopt incrementally new products. Studies 2 and 3 conceptually replicate these findings using situationally activated mindsets and demonstrate that this effect is driven by the perceived fit between the product's newness level and the optimal level of distinctiveness consumers want. Finally, Studies 4a and 4b show that the presence of distinctiveness-dampening cues (i.e., popularity cues) and distinctiveness-enhancing cues (i.e., scarcity cues) can reverse the effect of self-perspective such that the independent self becomes less willing to adopt really new products and more willing to adopt incrementally new products than does the interdependent self. These findings offer practical implications for managing innovation adoption in both domestic and international marketplaces.